Reliability and Validation of the Child Eating Behavior Questionnaire in 3- to 6-Year-Old Spanish Children - Jimeno-Martínez, Andrea; Maneschy, Ivie; Moreno, Luis A.; Bueno-Lozano, Gloria; De Miguel-Etayo, Pilar; Flores-Rojas, Katherine; Jurado-Castro, Jose Manuel; de Lamas, Carmela; Vázquez-Cobela, Rocio; Martinez-Lacruz, Raúl; Portoles, Olga; Martínez, J. Alfredo; et al. (Frontiers in Psychology, 2022)
Eating behavior is often established during the first years of life. It is important to research on it to understand the relationships that children have with food and how this can contribute to prevent the development of childhood obesity. An appropriate assessment of eating behavior can be achieved using the “Child Eating Behavior Questionnaire” (CEBQ). This questionnaire has been validated in several languages, but it has never been translated, adapted, and validated for Spanish children. The aim of the study is to evaluate the reliability and internal consistency of the CEBQ, culturally adapted and translated, in Spanish families with children aged 3 to 6 years, as well as its association with children’s body mass index (BMI) to test its construct validity. To achieve this, children were recruited from the ongoing MELI-POP randomized controlled clinical trial, as well as from public schools located in middle class neighborhoods of Zaragoza, Spain, to complete the sample. Sociodemographic characteristics and anthropometric measures were obtained. The 35-item CEBQ questionnaire was completed twice with a time difference between each response. Statistical analyses included the evaluation of internal consistency and reliability of the questionnaire, a confirmatory factor analysis, and the association between the different CEBQ scales and the children’s BMI. A total of 197 children completed variables; 97 of them were boys and 100 girls. There was a good internal consistency (Cronbach alpha with an average of 0.79 and greater than 0.5 in all items, except for question number 13); and a high test-retest reliability of the questionnaire with values with an average of 0.66. A gradual positive association was found between the score of different “pro-intake” scales of the CEBQ: “Food Responsiveness", “Emotional Overeating” and "Enjoyment of food" and the children’s BMI; at the opposite, negative associations were observed between BMI and the score of “anti-intake” scales "Satiety Responsiveness”, “Slowness in Eating” and “Emotional Undereating”. The Spanish version of the CEBQ is a useful tool to assess the eating behavior of Spanish children because the high reliability and internal validity. There is a significant association between eating behavior and BMI in Spanish children.